CARICOM : policy options for international engagement - Hall, Kenneth O. (Ian Randle KingstonJM, 2010)
Posits that CARICOM needs a more structured foundation for maximising the multiplier effects of collective representation and for leveraging CARICOM's diplomatic efforts and resources in a more coordinated and integrated manner.